Analysis of autonomic outcomes in APOLLO, a phase III trial of the RNAi therapeutic patisiran in patients with hereditary transthyretin-mediated amyloidosis - González-Duarte, Alejandra (2020)
Hereditary transthyretin-mediated (hATTR) amyloidosis is a progressive, debilitating disease often resulting in early-onset, life-impacting autonomic dysfunction. The effect of the RNAi therapeutic, patisiran, on autonomic neuropathy manifestations in patients with hATTR amyloidosis with polyneuropathy in the phase III APOLLO study is reported. Patients received patisiran 0.3 mg/kg intravenously (n = 148) or placebo (n = 77) once every 3 weeks for 18 months. Patisiran halted or reversed polyneuropathy and improved quality of life from baseline in the majority of patients. At baseline, patients in APOLLO had notable autonomic impairment, as demonstrated by the Composite Autonomic Symptom Score-31 (COMPASS-31) questionnaire and Norfolk Quality of Life-Diabetic Neuropathy (Norfolk QOL-DN) questionnaire autonomic neuropathy domain. At 18 months, patisiran improved autonomic neuropathy symptoms compared with placebo [COMPASS-31, least squares (LS) mean difference, - 7.5; 95% CI: - 11.9, - 3.2; Norfolk QOL-DN autonomic neuropathy domain, LS mean difference, - 1.1; - 1.8, - 0.5], nutritional status (modified body mass index, LS mean difference, 115.7; - 82.4, 149.0), and vasomotor function (postural blood pressure, LS mean difference, - 0.3; - 0.5, - 0.1). Patisiran treatment also led to improvement from baseline at 18 months for COMPASS-31 (LS mean change from baseline, - 5.3; 95% CI: - 7.9, - 2.7) and individual domains, orthostatic intolerance (- 4.6; - 6.3, - 2.9) and gastrointestinal symptoms (- 0.8; - 1.5, - 0.2). Rapid worsening of all study measures was observed with placebo, while patisiran treatment resulted in stable or improved scores compared with baseline. Patisiran demonstrates benefit across a range of burdensome autonomic neuropathy manifestations that deteriorate rapidly without early and continued treatment.